NUTRIENT UPTAKE AND CHEMICAL PROPERTIES OF SOIL AFTER HARVEST OF BABY CORN (Zea mays L.) AS INFLUENCED BY ORGANIC MANURES AND FERTILIZERS - D.H. ROOPASHREE,; S .KAMAL BAI . NAGARAJU,; S. RAGHAVENDRA, (The Bioscan, 2020)
An experiment was conducted during Kharif season, to study the effect of combination of different source and dosage of organic manures with fertilizers on nutrients uptake, available nutrients and chemical properties of soil after harvest of baby corn and its effect on yield of baby corn. Results revealed that, application of recommended dose of fertilizer along with FYM (150:75:40 kg N: P 2 O 5 :K 2 O ha -1 ) + 10 t FYM recorded significantly higher uptake of nitrogen, phosphorus and potassium (204.24, 35.23 and 213.6 kg/ha, respectively than applying only recommended dose of fertilizer. In same way, application of 100% N through different sources of organic manures, application of FYM + balance P and K through fertilizer significantly recorded next higher available nitrogen, phosphorus and potassium (233.5, 33.0 and 226.8 kg/ha, respectively) compared to other combinations of organic manure treatments. The same trend was noted with respect to yield. Highest baby corn yield (17.67q ha -1 ) and green fodder yield (36.53 t ha -1 ) was recorded in treatment where application of organic manure through FYM in combination of recommended dose of fertilizer (150:75:40 kg N: P 2 O 5 :K 2 O ha -1 ) + 10 t FYM was applied. Organic carbon content of soil was improved where organic manures along with fertilizers were applied.